High-dose melphalan-based sequential conditioning chemotherapy followed by allogeneic haematopoietic stem cell transplantation in adult patients with relapsed or refractory acute myeloid leukaemia - Steckel, Nina Kristin; Groth, Christoph; Mikesch, Jan-Henrik; Trenschel, Rudolf; Ottinger, Hellmut; Kordelas, Lambros; Müller-Tidow, Carsten; Schliemann, Christoph; Reicherts, Christian; Albring, Joern C.; Silling, Gerda; Schmidt, Eva; et al. (British journal of haematology, 2018)
Considering the unsatisfactory results of salvage therapies for patients with relapsed/refractory acute myeloid leukaemia (R/R-AML), their value before allogeneic haematopoietic stem cell transplantation (HSCT) remains questionable. However, direct allogeneic HSCT following established conditioning regimens applied in patients with R/R-AML during active disease has been equally disappointing. In this retrospective observational study, high-dose melphalan, as part of a sequential preparative regimen, followed by a total body irradiation (4 × 2 Gy)-based or a treosulfan-based dose-adapted conditioning therapy for allogeneic HSCT was administered to 292 adult patients (median age 56 years, range 17-74) with primary refractory (144 patients), secondary refractory (97 patients) or relapsed AML (51 patients). Overall survival rates at 3 years were 34%, 29% and 41%, respectively. Risk factors associated with an inferior survival were higher age, transplantation from a human leucocyte antigen-mismatched donor and high disease burden. Patients transplanted with blast infiltration <20% showed a notable survival rate of 51% at 3 years. In particular, patients with primary refractory AML showed a more favourable outcome when transplanted early during their disease course. Thus, high-dose melphalan-based sequential conditioning chemotherapy followed by an allogeneic HSCT is feasible and enables long-term remission to be achieved in a substantial proportion of patients with active R/R-AML.